The Effects of Use Nigella Sativa and / or Trigonella Foenum Graecum Seeds as Feed Supplemtations on Some Wool Growth and Its Physical Traits of Awassi Male Lambs: M.J.AL-Saadi1, M.N.AL-Saigh2 , D.Adulameer2 and S.B.AL-Araji3 - AL-Saadi1, M. J. (The Iraqi Journal of Veterinary Medicine, 2012)
The experiment was carried out at animal farm, College of Veterinary Medicine, Baghdad University from 1/July /2009 up to 28/February2010.Twenty Awssi male Lambs were equally divided into four groups and each animal fed on concentrate diets 2% of body weight with grazing for 3-5 hours a day. The first group(C) was kept as control group , the second group (N) was daily fed with same amount of concentrate diet contain 7.5% ground Nigella sativa seeds , third group (F) also fed with same amount contain 7.5% ground fenugreek seeds ,while the fourth group(NF) group fed the 2% concentrate diet supplemented with both (7.5% of Nigella sativa and 7.5% fenugreek seeds respectively ) as group feeding .The results revealed that using Nigella sativa or Fenugreek seeds as well as using both of them as a mixed feed supplemented with concentrated diet of Awassi ram lambs showed significantly ( P< 0.05 ) increasing and improvements in greasy wool weights , clean wool weights ,wool fiber lengths ,wool staple lengths ,wool fiber diameters compare with control group while NF group recorded significantly ( P< 0.05 ) higher than both of F and N groups in all of these parameters.